Implementasi Model Connected dalam Pembelajaran Tematik Terpadu di SD - yulia sari; Yanti Fitria; Yeni Erita (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Integrated thematic learning is learning that can combine existing concepts in learning. In learning in elementary schools there are several obstacles in the teacher's understanding regarding the appropriate and various learning models used. As a result, learning becomes less interesting, students have difficulty understanding the material, learning outcomes are low, and learning has no meaning for students. Teachers' lack of understanding of appropriate and varied learning models in the learning process is the main problem at this time. One learning model that can be applied to overcome this problem is the learning modelconnectedThe method used in this research is library research, where data collection is carried out by collecting some research on the implementation of learning models.connected in integrated thematic learning. From some of the research that has been collected, it can be concluded that there is a significant increase in student learning outcomes by applying or implementing learning modelsconnected in learning especially in integrated thematic learning. This is due to the learning modelconnected it integrates various fields of science so that it makes it easier for students to understand the objectives and learning materials. Understanding the learning modelconnected must be understood by every teacher because it is one of the reference learning models in integrated thematic learning.